Seismic evidence for a tilted mantle plume and north-south mantle flow beneath Iceland - Shen, Yang; Solomon, Sean C.; Bjarnason, Ingi Th; Nolet, Guust; Morgan, W. Jason; Allen, Richard M.; Vogfjörd, Kristin; Jakobsdóttir, Steinun; Stefánsson, Ragnar; Julian, B. R.; Foulger, G. R. (Earth and Planetary Science Letters, 2002)
Shear waves converted from compressional waves at mantle discontinuities near 410- and 660-km depth recorded by two broadband seismic experiments in Iceland reveal that the center of an area of anomalously thin mantle transition zone lies at least 100 km south of the upper-mantle low-velocity anomaly imaged tomographically beneath the hotspot. This offset is evidence for a tilted plume conduit in the upper mantle, the result of either northward flow of the Icelandic asthenosphere or southward flow of the upper part of the lower mantle in a no-net-rotation reference frame. © 2002 Elsevier Science B.V. All rights reserved.